Liquid Phase Depolymerization of Neyveli Lignite Over Phosphotungstic Acid - KRISHNAMURTHY , N.; PALANICHAMY , M.; CHELLAMANI , A.; ARUL LEO BASTIN , J.; MADASAMY , M.; VALLINAYAGAM , P.; MADHAVAN , D. (Asian Journal of Chemistry, 2013)
Neyveli lignite was depolymerized with phenol using phosphotungstic acid as catalyst at 185 ºC. The degree of depolymerization was determined by estimating the pyridine soluble portion in the product. Maximum pyridine extractability was 60.61 %. The effect of reaction parameters such as catalyst loading, phenol content and reaction time were studied for high degree of depolymerization. The IR spectrum of depolymerized lignite showed an intense peak for phenolic C-O stretching vibration in support of depolymerization. 1H NMR spectrum of depolymerized lignite also showed an increase in intensity for the signals due to aromatic ring. The TGA results illustrated reduced decomposition temperature for depolymerized product. The present study reveals phosphotungstic acid as an active catalyst for depolymerization of Neyveli lignite.